Dzahirat al-Tarjamah wa Waqi’u Tawhid al-Mushthalahat al-‘Arabiyah fi Mu’jam Covid-19 - Bahri, Ratni Bt. Hj.; Damhuri, Damhuri; Aman, Rahim Bin (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This research aimed to describe types of translation and the phenomenon of term unification in the covid-19 dictionary. This was a descriptive qualitative research with a content analysis approach. Data were collected through intensive reading of the covid-19 dictionary to find out translation types in that dictionary. Meanwhile, to gain a description of the term unification, it was done by confirming terms in the covid-19 dictionary to terms that existed in Mu’jam al-Thibbi al-Muwahhad in both printed and digital versions. The research findings indicated that the terms in the Covid-18 dictionary are the translations of English and French terms. In constructing the terms, there are several translation types. Those are direct translation with formal and semantic adjustment, literal translation with matched meaning yet different in its formal form, translation by creating new terms in the target language, descriptive translation, and the combination of translation and Arabization, Arabization and adjustment, and Arabization with no adjustment. In addition, from term unification, some categories were found, namely: standardized terms category, different from standardized terms category, unstandardized terms category, and unavailable terms in Mu’jam al-Thibbi al-Muwahhad category.